1961
DOI: 10.1126/science.133.3464.1594
|View full text |Cite
|
Sign up to set email alerts
|

Pollination of Saguaro Cactus by Doves, Nectar-Feeding Bats, and Honey Bees

Abstract: In a large cage, free-flying western white-winged doves, nectar-feeding Leptonycteris bats, and honey bees were each effective as cross-pollinators of self-sterile saguaro flowers. Seed production and seed viability were not significantly different in fruit from flowers pollinated by these agents. Pollination is not a limiting factor in saguaro repopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 2 publications
2
23
0
2
Order By: Relevance
“…The results of the pollination experiments showed that P. gaumeri is an obligate cross-pollinator, which concurs with reports on diverse species of columnar cacti (Alcorn et al, 1959(Alcorn et al, , 1961McGregor et al, 1962;Nassar et al, 1997;ValienteBanuet et al, 1997a;Casas et al, 1999). In the plants studied, self-pollination with and without manipulation did not produce fruit.…”
Section: Article In Presssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the pollination experiments showed that P. gaumeri is an obligate cross-pollinator, which concurs with reports on diverse species of columnar cacti (Alcorn et al, 1959(Alcorn et al, , 1961McGregor et al, 1962;Nassar et al, 1997;ValienteBanuet et al, 1997a;Casas et al, 1999). In the plants studied, self-pollination with and without manipulation did not produce fruit.…”
Section: Article In Presssupporting
confidence: 91%
“…In the former, the number of diurnal (mainly bees and birds) and nocturnal (bats) visitors during the flowering season was significantly higher than in the latter. In the Sonora Desert, it was reported that fruit set induced by bees and birds fluctuates between 58% and 81% (Alcorn et al, 1959(Alcorn et al, , 1961Fleming et al, 1994Fleming et al, , 1996. In the Tehuacan-Cuicatlan Valley, most of the species depend on bats as pollinators and subsequent fruit set fluctuates between 90% and 98% (Valiente-Banuet et al, 1996, 1997a.…”
Section: Introductionmentioning
confidence: 96%
“…En las cactáceas predominan las especies con sistemas de entrecruza y xenogamia obligada (Gibson y Nobel, 1986;Pimienta-Barrios y del Castillo, 2002;Godínez-Álvarez et al, 2003). A nivel de entrecruza se ha reportado que al menos 20 especies de cactáceas de la tribu Pachycereeae tienen un sistema de apareamiento xenógamo (Alcorn et al, 1961;Suzán et al, 1994;ValienteBanuet et al, 1997;Casas et al, 1999;Cruz y Casas, 2002;Clark-Tapia y Molina-Freaner, 2004;Molina-Freaner et al, 2004;Ibarra-Cerdeña et al, 2005;Méndez et al, 2005;Oaxaca-Villa et al, 2006).…”
Section: Discussionunclassified
“…The diurnal honey bee ( Apis mellifera ), the nocturnal nectar-feeding Mexican long-nose bat ( Leptonycteris nivalis ) and the white-winged dove ( Zenaida asiatica mearnsi ) are the most important pollinators. Zenaida , however, pollinates the giant cactus only (Alcorn et al 1959(Alcorn et al , 1961McGregor et al 1962 ). On the other hand, in the Magaliesberg mountain range (South Africa) opportunistic avian nectarivores, such as the Cape rock thrush ( Monticola rupestris ), have been found to enhance reproduction in an endemic montane aloe ( Aloe peglerae ) more than do specialized bird pollinators (Area et al 2013 ).…”
Section: Animals As a Cause Of Changes In Habitat Qualitymentioning
confidence: 99%